PENGGUNAAN RANGKAIAN BOOSTER CONVERTER DAN IC-TP4056 UNTUK LAMPU JALAN MURAH - Ricki Ananda; Wiwin Handoko (STMIK Royal, 2020)
Abstract: PJU (Public Street Lighting), is regulated in the regulation of the Minister of Transportation of the Republic of Indonesia Number 27 of 2018, concerning street lighting. In line with the statement of the village minister, development of underdeveloped areas and transmigration (Mendes PDTT), eko putro Sandjojo, said that village funds could be used to make street lamps for villages that do not have street lights. The area of the northern ring road, sub-district of datuk bandar timur in the direction of the port of Teluk Nibung, part of the road has no street lighting at night, plus the road conditions are still classified as red soil. Based on the results of field observations, the team researched making cheap street lamps, by utilizing the basic work system of the joule tief circuit, where the input is 7.4 VDC (in 3.7VDC arranged in series-parallel) with a lamp load of 12 watts multiplied by 4 lamps, with a total load. 48 watts, get the frequency measurement results of 12.30 Khz and Iout 0.14A, and Vpk-pk 82 V. Charging input is 7.4VDC, the current 19800mAh in the battery is divided by the maximum current of the solar module 1 watt, which is 160mA, so the charging time the battery is in the range of 2.1 hours. For the design of the lampposts that were made, using a paralon pipe with a length of 5m, with a circle diameter of 9cm, and a second pole connecting 1.5 m long with a circle diameter of 5cm. Keywords: Cheap street lights; joule tief series; 1 watt solar panel Abstrak : PJU (Penerangan Jalan Umum), diatur dalam peraturan mentri perhubungan republik indonesia nomor 27 tahun 2018, tentang alat penerangan jalan. Sejalan dengan pernyataan mentri desa, pembangunan daerah tertinggal dan transmigrasi (Mendes PDTT) eko putro Sandjojo, mengatakan bahwa dana desa bisa digunakan untuk membuat lampu jalan bagi desa yang tidak memiliki lampu jalan. Wilayah jalan lingkar utara, kecamatan datuk bandar timur searah menuju pelabuhan teluk nibung, sebahagian dari jalan tersebut tidak memiliki penerangan jalan dimalam hari, ditambah dengan kondisi jalan yang masih tergolong tanah merah. Berdasarkan hasil pengamatan dilapangan maka tim meneliti membuat lampu jalan murah, dengan memanfaatkan dasar sistem kerja rangkaian joule tief, dimana untuk input 7,4 VDC (in 3,7VDC disusun seri-paralel) dengan beban lampu 12 watt dikalikan 4 lampu, dengan total beban 48 watt, mendapati hasil pengukuran frequensi 12,30 Khz dan Iout 0,14A, dan Vpk-pk 82 V. Pengisian input 7,4VDC didapati, arus 19800mAh pada baterai dibagi dengan arus maksimum modul surya 1 watt, yaitu 160mA, sehingga lama pengisian baterai berada pada rentang waktu 2,1 jam. Untuk rancangan tiang lampu yang dibuat, menggunakan pipa paralon dengan panjang 5m, dengan diameter lingkaran 9cm, dan penyambung tiang kedua sepanjang 1,5 m dengan diameter lingkaran 5cm. Kata Kunci : Lampu jalan murah; rangkaian joule tief; panel surya 1 watt